2020
DOI: 10.3390/plants9101326
|View full text |Cite
|
Sign up to set email alerts
|

Root System Architecture, Copper Uptake and Tissue Distribution in Soybean (Glycine max (L.) Merr.) Grown in Copper Oxide Nanoparticle (CuONP)-Amended Soil and Implications for Human Nutrition

Abstract: Understanding the potential uptake and biodistribution of engineered nanoparticles (ENPs) in soil-grown plants is imperative for realistic toxicity and risk assessment considering the oral intake of edibles by humans. Herein, growing N-fixing symbiont (Bradyrhizobium japonicum) inoculated soybean (Glycine max (L.) Merr.) for a full lifecycle of 120 days, we assessed the potential influence of particle size (25, 50, and 250 nm) and concentration (0, 50, 100, 200, and 500 mg/kg soil) of Copper oxide nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 85 publications
1
19
0
Order By: Relevance
“…In this study, Cu inhibited the activity of NR and N assimilation in the stressed plants, and maximum reduction was observed in the plants raised with Cu (60 mg kg –1 ). The deduction may be due to reduced uptake of N by the roots, dysfunction of the enzyme under excess Cu conditions, alterations in membrane fluidity and composition ( Llorens et al, 2000 ) and root architecture ( Yusefi-Tanha et al, 2020 ), and metabolic dysfunction of the protein enzyme involved in nitrogen assimilation ( Hippler et al, 2018 ). However, the application of MEL mitigated the adverse effect induced by Cu and improved the activity of NR and N content ( Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Cu inhibited the activity of NR and N assimilation in the stressed plants, and maximum reduction was observed in the plants raised with Cu (60 mg kg –1 ). The deduction may be due to reduced uptake of N by the roots, dysfunction of the enzyme under excess Cu conditions, alterations in membrane fluidity and composition ( Llorens et al, 2000 ) and root architecture ( Yusefi-Tanha et al, 2020 ), and metabolic dysfunction of the protein enzyme involved in nitrogen assimilation ( Hippler et al, 2018 ). However, the application of MEL mitigated the adverse effect induced by Cu and improved the activity of NR and N content ( Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, different effects on plants’ operations can be caused by NPs of the same type but different sizes or shapes. For example, small-sized CuO NP (25 nm) led to increased Cu uptake in seeds and significantly improved Cu content in soybean seeds, despite reduction in root size [ 15 ]; these effects were not reported for larger-sized CuO NPs (50 nm and 250 nm) nor Cu 2+ ions. The same group of authors also reported differences in efficiency of different shaped ZnO NPs (spherical vs. floral-like vs. rod-like) on antioxidant defense systems and seed yield in soybeans [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of nanomaterials in agriculture has garnered widespread interest. Previous study showed that about 63–91% of the nanomaterials ended up in landfills, 8–28% in soils, and nanomaterials in the atmosphere get deposited on the surfaces of land and water. , Nearly 9% of nanoproducts are used in agricultural nanomaterials and nanocides; copper oxide nanoparticles (CuO NPs) are widely used in agricultural fungicides due to their bacteriostatic properties. CuO NPs have been demonstrated to be considerably effective in controlling plant diseases as they cause mechanical damage to cell biofilm development, which is toxic to bacteria. In addition, CuO NPs are considered to be one of the most essential engineered NPs; the growing use and demand for recycled waste water for irrigation has opened up the possibility of releasing CuO NPs into paddy soil via waste water. , CuO NPs are also used as plant growth promoters to enhance the uptake of iron (Fe), calcium, magnesium, and phosphorus in agriculture. , Although CuO NPs are generally recognized as safe salts (GRAS, the FDA’s safety index for food additives), a high dose of CuO NPs (50–1000 mg kg –1 ) significantly increased excessive oxidative stress, inhibited root growth, and decreased the crop yield. Therefore, the extensive or large-scale use of CuO NPs in paddy soil requires further studies.…”
Section: Introductionmentioning
confidence: 99%